Grain size dependence of hardness and fracture toughness in pure near fully-dense boron carbide ceramics - Moshtaghioun, BM; Gomez-Garcia, D; Dominguez-Rodriguez, A; Todd, RI (European Ceramic Society, 2016)
Room temperature fracture toughness and hardness of spark plasma sintered pure B4C ceramics with grain sizes ranging from 120 nm to 17 μm have been studied. Vickers indentation and single edge V-notched beam (SEVNB) techniques have been used to measure hardness and fracture toughness, respectively. A critical analysis of the results derived from these two techniques has been carried out and the conditions for proper comparison of the derived results are discussed. The results have shown that hardness follows the Hall–Petch dependence with either grain size or twin spacing when the effect of porosity is corrected for. On the contrary, fracture toughness is found to be essentially grain size independent. The value of this quantity is ∼2 MPa m1/2.